Effects of subclinical hypothyroidism on maternal and obstetric outcomes during pregnancy - Genç, Simten; Cıngıllıoğlu, Başak (The European Research Journal, 2022)
Objectives: Subclinical hypothyroidism has been defined as normal free thyroxine (FT4) with elevated thyroid stimulating hormone (TSH) levels. The aim of this study is to examine the relationship between the first trimester subclinical hypothyroidism with adverse obstetric outcomes in pregnant women. Methods: This retrospective cohort study was conducted by examining the pregnant women who applied to the Gynecology Department of Okmeydani Training and Research Hospital at their 6th to 14th gestational weeks and had antenatal follow-ups between February 1, 2017 and December 31, 2020. Results: Fetal weight (OR: 1; 95% CI, 0.99-1.03, p = 0.023), gestational age at delivery (OR: 0.91; 95% CI, 0.83-0.99, p = 0.022), and preterm delivery (OR: 0.79; 95% CI, 0.48-1.06, p = 0.005) were found to be statistically significant parameters in univariate risk analyses performed in the group whith patients normal T4 levels and TSH levels ≥ 2.5-4 mIU/L. Lower gestational age at delivery (OR: 1; 95% CI, 0.93-1.88, p = 0.016), and higher preterm delivery rates (OR: 0.99; 95% CI, 0.96-1.01, p = 0.003) were found to be statistically significant in multivariate risk analysis. Conclusions: The rate of preterm delivery was statistically higher, and fetal weight and week of delivery were significantly lower in the group of pregnant women diagnosed with SCH having TSH values between 2.5 and 4 mIU/L.